Love as a reward for the feat: the interpretation of love in the North French knightly romance - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
The article discovers the peculiarities of the interpretation of love in a medieval knight romance. The place of the love line in the plot structure of romance is identified. The specifics of the understanding of love in the novels of the Arthurian and Tristan cycles are revealed.